Electronic Government as a Vector of Innovative State Transformations in Russia - Pavlyutenkova, M Y (Vestnik Rossijskogo universiteta družby narodov. Seriâ Politologiâ (Online), 2016)
This article considered conceptual and administrative aspects of the e-government, traces the evolution of the interpretation of the term “the using of information technologies in functioning of public administration” to “collaborative public governance”. It is shown that in Russia, which is in conditions of an economic crisis and a difficult foreign policy situation, strengthened by the sanctions imposed against it, the decisions of “the electronic government” can become essential part of strategy of innovative public administration.